Anti-Corruption Education At IT Al Multazam High School, Kuningan District - Mahmud; Elva Siti Fatimah; Fiqih Fazriyansyah; Mohamad Erihadiana (STAI Miftahul Ula Nganjuk, 2024)
This study aims to present aboutacquire knowledge about anti-corruption, and if it is related to the values ??of defending the country, then having anti-corruption principles is a form or implementation of defending the country. The methodology or approach used in this study is a quantitative approach method, while data collection was carried out bypre-testand post-test.The findings in this study namelythe results obtained from the pre-test and post-test given to 41 students obtained an average pre-test score of 70.24 and an average score on the post-test results of 89.02, with an average increase of 18.78 after being given education anti Corruption.Can be concluded thatThis anti-corruption education program is considered effective for students, because with the education received by students, it can be disseminated to family and peers. Keywords: Education; Anti Corruption; Man